839 Patterns of Management of Acute Cholecystitis during the COVID 19 Pandemic. (12th October 2021) - Brown, B; Varley, R; Reynolds, E; Galloway, S
Abstract: Aim: The poor outcomes described by CovidSurg in patients with Covid-19 undergoing surgical intervention and the unknown safety of laparoscopic surgery initially led to increased conservative management in acute cholecystitis (AC). As the number of cases continues to rise, we aim to assess how the coronavirus pandemic has affected our service and adherence to AUGIS guidelines. Method: We retrospectively analysed all adult admissions with radiologically confirmed AC from defined 2-month periods (pre-pandemic (PP), wave-1 (W1) and wave-2 (W2)) at an acute general surgical service without dedicated hot gallbladder lists where the prevalence of coronavirus has remained high throughout. Primary outcome was rate of index admission (acute) cholecystectomy. Results: 93 patients were included in total (PP 35, W1 33, W2 24). Demographic details were similar across all groups. Tokyo grade I (mild) cholecystitis was more commonly admitted PP (63.9% versus 48.5% and 50.0%). Conservative management was trialed in 91.7%, 100.0% and 62.5% and failed in 18.2%, 21.2% and 21.1%. Cholecystectomy rates were 13.9%, 12.1% and 29.2%. Increased use of CT in W1 has returned to PP imaging pattern in W2. 30-day readmission rates were 5.6%, 18.2% and 4.2%. Two patients in W1 tested positive for Covid-19 and were managed conservatively. No post-operative pulmonary complications were recorded and no difference in biliary complications was observed. Conclusions: Operative management of AC as per AUGIS guidelines during the pandemic in Covid-19 negative patients is safe and improves outcomes compared to conservative management with no appreciable increase in biliary complications.